Cyanosis with hepatic cirrhosis: A case with pulmonary arteriovenous shunting. Issue 6 (November 1967) - Karlish, A. J.; Marshall, R.; Reid, Lynne; Sherlock, Sheila
Abstract : A case is reported of cirrhosis of the liver associated with cyanosis and finger clubbing in a man of 31 years. The chest radiograph showed diffuse nodular shadows in both lower zones. Pulmonary function tests gave an arterial oxygen saturation of 91% at rest, falling to 68% on exercise; the single breath diffusing capacity for carbon monoxide was reduced to 55% of the predicted value and there was an estimated right-to-left shunt of 23%. Post-mortem injection of the lungs with Micropaque-gelatin suspension showed numerous pleural spider naevi, denser over the lower lobes, arteriovenous communications in the infrahilar regions, including leashes of dilated vessels in pleural adhesions on the diaphragm and diffuse arterial vasodilatation in the lungs; although the injection mass could be traced into the pulmonary veins in only a few regions of the lung, the dilated arterioles and spiders were possible additional channels through which blood might be shunted from the alveolar surfaces. The very low arterial oxygen saturation on exercise was probably caused by a shunt greater than the 23% estimated at rest, but the low diffusing capacity may have been partly responsible. The cause of the low diffusing capacity remains uncertain.